2018
DOI: 10.1002/ange.201809411
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Promiscuity of Galactose Oxidase: A Mild Synthesis of Nitriles from Alcohols, Air, and Ammonia

Abstract: We report an unprecedented catalytically promiscuous activity of the copper‐dependent enzyme galactose oxidase. The enzyme catalyses the one‐pot conversion of alcohols into the related nitriles under mild reaction conditions in ammonium buffer, consuming ammonia as the source of nitrogen and dioxygen (from air at atmospheric pressure) as the only oxidant. Thus, this green method does not require either cyanide salts, toxic metals, or undesired oxidants in stoichiometric amounts. The substrate scope of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Overall, the broad substrate scope covered by these recently characterized fungal enzymes highlights the catalytic potential within the AA5_2 protein family. A striking example of such catalytic promiscuity was recently unveiled in a variant of Fgr GalOx, unlocking the production of nitriles from alcohols in the presence of ammonia . Yet, despite their intrinsic and unique biocatalytic abilities, and in contrast to ADH and AOX systems or archetypal Fgr GalOx and its engineered variants that have been harnessed for multiple applications, , CRO-AlcOx have hitherto received little attention as biocatalysts for the oxidation of industrially relevant alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the broad substrate scope covered by these recently characterized fungal enzymes highlights the catalytic potential within the AA5_2 protein family. A striking example of such catalytic promiscuity was recently unveiled in a variant of Fgr GalOx, unlocking the production of nitriles from alcohols in the presence of ammonia . Yet, despite their intrinsic and unique biocatalytic abilities, and in contrast to ADH and AOX systems or archetypal Fgr GalOx and its engineered variants that have been harnessed for multiple applications, , CRO-AlcOx have hitherto received little attention as biocatalysts for the oxidation of industrially relevant alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since their discovery in 1959, the founding member of CROs, namely the galactose oxidase (EC 1.1.3.9) from Fusarium graminearum (FgrGalOx) has been the main object of most studies. Numerous applications have been described for the FgrGalOx and the boundaries of its substrate specificity have been pushed far beyond its natural carbohydrate preference (Birmingham and Turner, 2018;Deacon et al, 2004;Escalettes and Turner, 2008;Herter et al, 2015;Mattey et al, 2020;McKenna et al, 2015;Sun et al, 2002;Vilím et al, 2018;Wilkinson et al, 2004). It is only recently, with the advent of natural diversity exploration, notably rendered possible by the availability of abundant genomic data, that the true potential of CROs scope of action was unveiled (Andberg et al, 2017;Mathieu et al, 2020;Mollerup et al, 2019;Paukner et al, 2015Paukner et al, , 2014Yin et al, 2015).…”
Section: Substrate Specificity Of Cro-alcoxmentioning
confidence: 99%
“…Nevertheless, nitriles are synthesized predominantly by addition or substitution of leaving groups by cyanide [4] . Cyanide salts are highly toxic, and therefore, cyanide free routes to nitriles are emerging [8] . The research groups of Asano and Gröger reported a number of cyanide‐free syntheses of (aryl‐)aliphatic nitriles by aldoxime dehydratases, including enantioselective reactions [9] .…”
Section: Introductionmentioning
confidence: 99%